2023
DOI: 10.1177/11779322221146651
|View full text |Cite
|
Sign up to set email alerts
|

Pyridine Derivatives as Potential Inhibitors for Coronavirus SARS-CoV-2: A Molecular Docking Study

Abstract: Coronavirus SARS-CoV-2, a causative agent for the global epidemic disease COVID-19, which has a highest modality rate. Several initiatives have been undertaken to repurpose current antiviral medications and tested the classic pyridine derivatives (PyDev), which have showed substantial therapeutic potential against a variety of illnesses and also have several biological functions such as, antibacterial, antiviral, and anti-inflammatory. However, limited reports are available for the treatment of Coronavirus SAR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Moreover, recent studies have shown promising results for the treatment of Coronavirus SARS-CoV-2 using pyridine derivatives. Terpyridine demonstrates potent binding efficacy against the SARS-CoV-2 spike glycoprotein [45], while bis-indolyl pyridines ef- Nitrogen-based heterocyclic chemistry plays a crucial role in small-molecular chemistry, demonstrating remarkable versatility and significance in various biological and pharmacological activities [36][37][38][39]. Specifically, our discovered inhibitors, namely C8 and its analogs (including C10), have a distinctive 1,3,5-triazine backbone and pyridine side of 14 chain.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Moreover, recent studies have shown promising results for the treatment of Coronavirus SARS-CoV-2 using pyridine derivatives. Terpyridine demonstrates potent binding efficacy against the SARS-CoV-2 spike glycoprotein [45], while bis-indolyl pyridines ef- Nitrogen-based heterocyclic chemistry plays a crucial role in small-molecular chemistry, demonstrating remarkable versatility and significance in various biological and pharmacological activities [36][37][38][39]. Specifically, our discovered inhibitors, namely C8 and its analogs (including C10), have a distinctive 1,3,5-triazine backbone and pyridine side of 14 chain.…”
Section: Discussionmentioning
confidence: 88%
“…Moreover, recent studies have shown promising results for the treatment of Coronavirus SARS-CoV-2 using pyridine derivatives. Terpyridine demonstrates potent binding efficacy against the SARS-CoV-2 spike glycoprotein [ 45 ], while bis-indolyl pyridines effectively hinder the infectivity of lentiviral vectors pseudotyped with spike glycoprotein. Further exploration of the interaction between bis-indolyl pyridines and spike RBD uncovered the formation of a hydrogen bond between Gly502 and one of the bis-indolyl pyridine ether groups [ 46 ].…”
Section: Discussionmentioning
confidence: 99%